Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881 - Lo, Yik-Fui Philip; Li, Fei; Ding, Liang (Zootaxa, 2017)
An insular population of Talicada nyseus was discovered from Hainan Island, representing a butterfly species unrecorded in China. Materials of this species from Hainan were compared with the races from other regions, revealing that the wing pattern is distinct from that of other subspecies, and is hereinto described as T. nyseus lami ssp. nov.. Information on immature stage and host association of the new subspecies, and notes on the genus is also provided.